2018
DOI: 10.21511/ppm.16(1).2018.14
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of emotional intelligence in the employees performance

Abstract: This study investigates the mediating effect of emotional intelligence on the relationship between motivation, compensation, satisfaction, work climate and employees’ performance. The sample consists of 96 field officials who were the government employees specializing in coping with the eradication of Dengue Hemorrhagic Fever (DHF) in the district of Jember, Indonesia. Results using path analysis reveal that all examined variables positively and significantly affect employees’ performance. The study finds that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…In contrast, studies have confirmed the negative impact of occupational stress on emotional intelligence [ 36 , 37 ]. A study reported the positive mediating effect of emotional intelligence in the relationship between occupational variables and the Job performance [ 38 ]. Hence, emotional intelligence can improve nurses’ job performance by mediating the negative effect of occupational stress on their performance.…”
Section: Conceptual Framework and Development Of Hypothesesmentioning
confidence: 99%
“…In contrast, studies have confirmed the negative impact of occupational stress on emotional intelligence [ 36 , 37 ]. A study reported the positive mediating effect of emotional intelligence in the relationship between occupational variables and the Job performance [ 38 ]. Hence, emotional intelligence can improve nurses’ job performance by mediating the negative effect of occupational stress on their performance.…”
Section: Conceptual Framework and Development Of Hypothesesmentioning
confidence: 99%
“…A study by Hendrawijaya, Gumanti and Puspitaningtyas (2018) examined the prominent factors that affect the employees' performance. The study used a sample of 96 government officials assigned to cope with Dengue Hemorrhagic Fever (DHF) in the District of Jember, Indonesia.…”
Section: Empirical Review Of Literaturementioning
confidence: 99%
“…Asimismo, se detectó que la IE tiene una relación significativa con el desempeño de los colaboradores, lo cual se refleja en el rendimiento de la organización, y tiene a la motivación como parte del proceso (Guajala, 2017;Kamassi et al, 2019;Chand et al, 2019;Sastre y Danvila, 2017;Rezvani et al, 2019;Miao et al, 2017;Boohene et al, 2019;Sony y Mekoth, 2016;Akintayo y Babalola, 2012;Hendrawijaya et al, 2018). Por otro lado, para Miao et al (2019), la IE se relaciona con la calidad del servicio por parte de los colaboradores, sin que el género marque distinción alguna.…”
Section: Introductionunclassified